Pengelolaan Pendidikan Moral dan Keterampilan Abad Ke-21 untuk Meningkatkan Daya Saing di Dunia Digital (Kecerdasan Buatan) - Muhammad Ressi; Saihan Saihan; Lailatul Usriyah (Instructional Development Journal, 2024)
:  This research aims to explore the management of moral education and skills in the 21st century in an effort to increase students' competitiveness in the digital world, especially in the context of artificial intelligence (AI) in SD IT Kuntum Insan Cemerlang, Bondoowoso. Through qualitative methods involving interviews with principals, teachers, and students, as well as observations in educational institutions, the study found that the integration of moral education with 21st century skills not only shapes students' character but also prepares them to face the challenges that arise from the use of advanced technology. Values such as responsibility, honesty, and empathy are recognized as essential foundations in the ethical use of technology, while skills such as critical thinking, creativity, collaboration, and communication are essential skills needed in the digital age.Despite implementation challenges, such as limited technology infrastructure and lack of training for teachers, the study also shows opportunities for development through collaboration with external parties and communities. Educational policies that support the integration of moral and skills education in the 21st century are essential to create an inclusive and responsive learning environment. The findings of this study confirm the need for a holistic approach in education that not only focuses on academic aspects, but also on the development of students' character and social awareness, so that they are ready to contribute positively in an increasingly complex and technology-based society.